2015
DOI: 10.1038/srep12065
|View full text |Cite
|
Sign up to set email alerts
|

Both TALENs and CRISPR/Cas9 directly target the HBB IVS2–654 (C > T) mutation in β-thalassemia-derived iPSCs

Abstract: β-Thalassemia is one of the most common genetic blood diseases and is caused by either point mutations or deletions in the β-globin (HBB) gene. The generation of patient-specific induced pluripotent stem cells (iPSCs) and subsequent correction of the disease-causing mutations may be a potential therapeutic strategy for this disease. Due to the low efficiency of typical homologous recombination, endonucleases, including TALENs and CRISPR/Cas9, have been widely used to enhance the gene correction efficiency in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 51 publications
3
132
1
1
Order By: Relevance
“…Traditional methods of gene correction rely on antibiotic selection and then removal of the marker, which is a lengthy process that increases the risk of generating additional genome instability in human iPSCs (20). CRISPR/Cas9-induced genome editing was recently performed in ␤-Thal iPSCs using a piggyBac or donor vector as the repair template (15,16).…”
mentioning
confidence: 99%
“…Traditional methods of gene correction rely on antibiotic selection and then removal of the marker, which is a lengthy process that increases the risk of generating additional genome instability in human iPSCs (20). CRISPR/Cas9-induced genome editing was recently performed in ␤-Thal iPSCs using a piggyBac or donor vector as the repair template (15,16).…”
mentioning
confidence: 99%
“…[77][78][79][80][81] One advantage of using iPSCs for gene correction is that it could then be possible to obtain a completely corrected clone of pluripotent stem cells, from which a large number of stem cells or other cells of interest could be derived for transplantation. However, so far it has not been possible to use iPSCderived HSCs to engraft and provide sustained hematopoiesis.…”
Section: Genome Editing For Gene Correctionmentioning
confidence: 99%
“…Moreover, upon screening 624 and 717 potential off-target sites for 12 sgRNA in 293FT cells and iPSCs, respectively, a total of three sites were identified as being associated with two sgRNAs only [87]. On the other hand, Xu et al [138] showed clear off-target activity at seven out of 10 sites after targeting Intron 2 of the HBB gene, and reported a comparable level of off-target activity in 293FT cells and iPSCs. The discrepancy between these studies may be related to the sequence of the sgRNA used and the local environment of the targeted locus.…”
Section: Evidence For Dna Repair At Off-target Sites In Ipscsmentioning
confidence: 97%
“…A number of studies have successfully used programmable engineered nucleases such as ZFNs, TALENs and RGNs for targeted repair of the disease-causing mutation in iPSCs derived from patients with monogenic disorders affecting the -globin gene, including sickle cell anaemia [140][141][142][143] and thalassaemia [26,35,36,38,138,144]. In contrast to ZFNs and TALENs, the Cas9 system offers the advantage of a higher targeting efficiency using a cost-effective, flexible and versatile system [8].…”
Section: Gene Editing In Beta-haemoglobinopathiesmentioning
confidence: 99%
See 1 more Smart Citation